2010
DOI: 10.1590/s1413-86702010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal gammopathy associated with visceral leishmaniasis

Abstract: Monoclonal gammopathy can accompany diverse conditions and is usually benign. It should be distinguished from monoclonal gammopathy of undetermined signifi cance (MGUS) which can rarely turn malignant. Visceral leishmaniasis has only rarely been associated with monoclonal gammopathy. We describe the case of a 55-year-old male who had monoclonal gammopathy associated with visceral leishmanisais, which reversed with stibogluconate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Sharma V et al revealed that higher levels of serum calcium are associated with less severity of acute ischemic stroke and also recorded a favorable outcome in these cases at 7 days. 11 In our study, there is negative correlation found between the calcium level and NIHSS of the patients i.e. r = -0.899.…”
Section: Figure-1supporting
confidence: 46%
“…Sharma V et al revealed that higher levels of serum calcium are associated with less severity of acute ischemic stroke and also recorded a favorable outcome in these cases at 7 days. 11 In our study, there is negative correlation found between the calcium level and NIHSS of the patients i.e. r = -0.899.…”
Section: Figure-1supporting
confidence: 46%